2010
DOI: 10.3141/2198-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Street Network Design on Walking and Biking

Abstract: The objective of this research was to investigate whether a relationship existed between street network characteristics and the transportation modes selected in a neighborhood. Factors such as street characteristics, vehicle volumes, activity levels, income levels, and proximity to limited-access highways and the downtown area were controlled for. The results suggested that all three of the fundamental characteristics of a street network—street connectivity, street network density, and street patterns—were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 13 publications
4
60
0
Order By: Relevance
“…24 It was found that low SES areas had higher scores for intersection density and land use mix that are known to be associated with walking for transport. 32,33 Increasing recreational walking may not be feasible in some low SES areas. Promoting walking for transport may be an alternative approach in such areas to address the health gap between SES areas.…”
Section: Discussionmentioning
confidence: 99%
“…24 It was found that low SES areas had higher scores for intersection density and land use mix that are known to be associated with walking for transport. 32,33 Increasing recreational walking may not be feasible in some low SES areas. Promoting walking for transport may be an alternative approach in such areas to address the health gap between SES areas.…”
Section: Discussionmentioning
confidence: 99%
“…Connectivity assesses the effectiveness of the urban form in facilitating the movement of humans and vehicles between destinations. Simulation studies have shown that a street network of high connectivity, a grid-like street pattern with minimal cul-de-sacs, will reduce fuel consumption [14], discourage driving, and encourage walking [15]. Empirical studies have also been conducted to substantiate these claims [16,17].…”
Section: Performances Affected By Changes In Urban Formmentioning
confidence: 99%
“…Similarly, Marshall and Garrick (2010) showed that fundamental characteristics of street network design such as connectivity, density, and patterns have an extremely important effect on encouraging non-motorized travel. As part of this analysis on metropolitan areas, it is important to quantify the structure of transit and other non-motorized networks, and to see how this affects the performance of the transportation system such as modal share.…”
Section: Limitationsmentioning
confidence: 99%